(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study examined the impact of Green Technical and Vocational Education and Training (TVET) and Artificial Intelligence (AI) in promoting sustainable development in technical colleges in Ogun State, Nigeria. It assessed the level of adoption of green practices and AI technologies, and their influence on environmental awareness, resource management, and students’ employability. A survey research design was adopted, involving 300 respondents comprising teachers, administrators, and senior students selected through stratified random sampling. Three hundred (300) questionnaire were generated to elicit response from respondents. Data were collected using the validated Green TVET and AI Integration Assessment Questionnaire (GTAIAQ) and analyzed using descriptive and inferential statistics. Alpha basis where a reliability coefficient of 0.70 or above is accepted. Findings revealed a moderate to high adoption of green TVET practices, particularly in environmental sustainability and green entrepreneurship, although gaps exist in eco-friendly instructional resources and renewable energy training. AI adoption was also moderate, with common applications including personalized learning and AI-powered assessment tools. However, inadequate infrastructure, financial constraints, policy limitations, and resistance to change hinder effective implementation.The study concluded that integrating Green TVET and AI significantly enhances sustainable development outcomes. It recommended increased investment in digital infrastructure, capacity building, and stronger collaboration among stakeholders to support effective implementation.